2011
DOI: 10.1002/lt.22416
|View full text |Cite
|
Sign up to set email alerts
|

Patients with non-[18F]fludeoxyglucose-avid advanced hepatocellular carcinoma on clinical staging may achieve long-term recurrence-free survival after liver transplantation

Abstract: There is increasing evidence that a relevant number of patients with hepatocellular carcinoma (HCC) exceeding the Milan criteria may benefit from liver transplantation (LT). We retrospectively analyzed the prognostic significance of [ 18 F]fludeoxyglucose ([ 18 F]FDG) positron emission tomography (PET) for identifying appropriate LT candidates with advanced HCC on clinical staging. Between 1995 and 2008, 111 patients with HCC were listed for LT. All underwent a pretransplant PET evaluation. LT was performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 40 publications
3
80
0
2
Order By: Relevance
“…In some previous studies, the metabolic status of HCC as seen on 18 F-FDG PET was the only significant factor predicting long-term survival (21) and early recurrence (,6 mo) after liver transplantation (22). Other studies found some additional factors to be significant, such as the metabolic status of the HCC, the extent of vascular invasion (23,24), and the degree of differentiation (23,24).…”
Section: Discussionmentioning
confidence: 95%
“…In some previous studies, the metabolic status of HCC as seen on 18 F-FDG PET was the only significant factor predicting long-term survival (21) and early recurrence (,6 mo) after liver transplantation (22). Other studies found some additional factors to be significant, such as the metabolic status of the HCC, the extent of vascular invasion (23,24), and the degree of differentiation (23,24).…”
Section: Discussionmentioning
confidence: 95%
“…The utility of 18-FDG-PET in determining tumor biology has been shown by Kornberg et al 80 . They reported that pre-OLT factors with high predictive value for recurrence-free survival were: negative PET uptake, AFP < 400 IU/mL and total tumor diameter < 10 cm.…”
Section: Tumor Biology: Anaspect To Be Included In the Criteriamentioning
confidence: 94%
“…Tumor biomarkers could contribute to overcome the restrictions of the conventional selection criteria, thereby increasing the number of the patients indicated for LDLT (27). One recent study (28) demonstrated a comparable 5-year recurrence-free survival rate between LDLT recipients whose tumors exceeded the Milan criteria but who had negative PET and recipients whose tumors met the Milan criteria (81% vs. 86%).…”
Section: Limitation Of Tumor Status In Ldltmentioning
confidence: 95%